Gnomes and sneezes - Citro, Asia; Lindsay, Marion (Seattle, WA : Innovation Press, 2024)
Pip shows up with a new look that's just as surprising to him as it is to Zoey and Sassafras. When they retrace Pip's steps in the forest, they see another magical friend change right before their eyes.
K-3
Keywords: Girls -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Cats -- Juvenile fiction; Magic -- Juvenile fiction; Girls -- Fiction; Imaginary creatures -- Fiction; Cats -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction; Frogs -- Fiction